The role of metformin and statins in the incidence of epithelial ovarian cancer in type 2 diabetes: a cohort and nested case–control study. (12th March 2018) - Urpilainen, E; Marttila, M; Hautakoski, A; Arffman, M; Sund, R; Ilanne‐Parikka, P; Arima, R; Kangaskokko, J; Puistola, U; Läärä, E; Hinkula, M
Abstract : Objective: To obtain evidence of the effects of metformin and statins on the incidence of ovarian cancer in women with type 2 diabetes (T2D). Design: A retrospective cohort study and nested case–control study. Setting: The data were obtained from a diabetes database (FinDM) combining information from several nationwide registers. Population: A cohort of 137 643 women over 40 years old and diagnosed with T2D during 1996–2011 in Finland. Methods: In full cohort analysis Poisson regression was used to estimate the hazard ratios (HR) in relation to ever use of metformin, insulin other oral anti‐diabetic medication or statins. In the nested case–control analysis 20 controls were matched to each case of ovarian cancer. Conditional logistic regression was used to estimate HRs in relation to medication use and cumulative use of different medications. The estimates were adjusted for age and duration of T2D. Main outcome measure: Incidence of ovarian cancer. Results: In all, 303 women were diagnosed with ovarian cancer during the follow up. Compared with other forms of oral anti‐diabetic medication, metformin (HR 1.02, 95% CI: 0.72–1.45) was not found to be associated with the incidence of ovarian cancer. Neither was there evidence for statins to affect the incidence (HR 0.99, 95% CI: 0.78–1.25). In nested case–control analysis the results were essentially similar. Conclusions: No evidence of an association between the use of metformin or statins and the incidence of ovarian cancer in women with T2D was found. Tweetable abstract: No evidence found for metformin or statins reducing the incidence of ovarian cancer. Tweetable abstract: No evidence found for metformin or statins reducing the incidence of ovarian cancer.